The erector spinae plane (ESP) block: A pooled review of 242 cases - Tsui, Ban C.H.; Fonseca, Ahtziri; Munshey, Farrukh; McFadyen, Grant; Caruso, Thomas J. (Journal of clinical anesthesia, 2019)
The erector spinae plane block (ESPB) was first described in 2016 as a regional block for thoracic neuropathic pain. Given its short history, there are a paucity of controlled clinical trials, yet an abundance of case reports. The primary aim of this review is to examine pooled clinical data from published literature to gain an understanding of ESPB characteristics. A PubMed search was conducted to identify all ESPB related publications. Inclusion criteria included reports of ESP single shot, continuous infusion, intermittent bolus, human and cadaveric studies. Only publications obtained in English were included. Measures included type of publication, year and country of publication, journal of publication, block technique, anatomic location, age, opioid and adjunct pain medication use, sensory and motor changes, side effects and adverse events. Qualitative statistics were used. The initial search yielded 201 publications. After application of inclusion and exclusion criteria, 85 publications from 21 journals were included in the pooled review which yielded 242 reported cases between 2016 and 2018. The majority of publications reported single shot techniques (80.2%), followed by intermittent boluses (12.0%) and continuous infusions (7.9%). 90.9% reported use of multimodal analgesia in addition to the ESPB and 34.7% reported sensory changes from ESPB. A reduction in opioid use was reported in 34.7% of cases. One adverse event involving a pneumothorax was reported. To our knowledge, this is the first review providing a pooled review of ESPB characteristics. The ESPB appears to be a safe and effective option for multiple types thoracic, abdominal, and extremity surgeries. •The rapid increase of publications from many countries indicates widespread adoption.•Reports have demonstrated analgesia at cervical, thoracic, and lumbar levels.•No cases of bleeding or hemodynamic effects